Program Interaktif Penunjang Pencegahan Stunting di Dusun Wulung, Desa Soronalan, Kabupaten Magelang - Noor Saputra, Abraham Qodry; Radya Naweswara, Clarisa; Dzahrah, Davina Maureen Marsandah; Hidayah, Latiefah Nur; Kurniasari, Pipit Dwi; Abriwiyanti, Putri Nazmah; Saputra, Rizki Kurniawan; Mulyaningsih, Tri (Universitas Baiturrahim, 2025)
Based on data from the Electronic Community-Basd Nutrition Recording and Reporting System (E-PPGBM) in Magelang Regency, the stunting rate decreased from 20.23% in 2020 to 14.76% in 2021 and further decline to 13.11% in 2022. However, in 2023 the rate increased again to 15.22%. Specifically, in Sawangan District as of November 2024, the stunting rate reached 19.7% with a total of 567 cases. Sawangan Village alone recorded a prevalence of 20.61%, accounting for 40 cases. The low intake of fruits and vegetables among children, along with cases of malnutrition in Wulung Hamlet, Soronalan Village, Sawangan District, Magelang Regency, became the main driving factors for organizing this series of interactive programs. These programs consist of nutrition food preparation sessions, nutritious food distribution, and socialization of the “Isi Piringku” concept. The aim of these programs is to encourage healthy and appealing food alternatives for children and to introduce the “Isi Piringku” module to help them better understand the concept of balanced nutrition. The Residents of Wulung Hamlet respnded very positively to the implemtation of these interactive programs as a part of the ffort to prevent stunting among children.